2018
DOI: 10.1111/exsy.12276
|View full text |Cite
|
Sign up to set email alerts
|

OWL‐based acquisition and editing of computer‐interpretable guidelines with the CompGuide editor

Abstract: Computer‐Interpretable Guidelines (CIGs) are the dominant medium for the delivery of clinical decision support, given the evidence‐based nature of their source material. Therefore, these machine‐readable versions have the ability to improve practitioner performance and conformance to standards, with availability at the point and time of care. The formalisation of Clinical Practice Guideline knowledge in a machine‐readable format is a crucial task to make it suitable for the integration in Clinical Decision Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Moreover, previous studies by Paavola and Hakkarainen (2005), Liao et al (2010), Maula et al (2010), Lopez-Nicolas and Soto-Acosta (2010), Pástor et al (2013) and Helal (2017) explored to some extent the relationship between knowledge acquisition and knowledge creation. However, these studies were conducted in non-academic environments and none of them studied and tested the variables used in this study to find the relationship between knowledge acquisition and knowledge creation.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies by Paavola and Hakkarainen (2005), Liao et al (2010), Maula et al (2010), Lopez-Nicolas and Soto-Acosta (2010), Pástor et al (2013) and Helal (2017) explored to some extent the relationship between knowledge acquisition and knowledge creation. However, these studies were conducted in non-academic environments and none of them studied and tested the variables used in this study to find the relationship between knowledge acquisition and knowledge creation.…”
Section: Problem Statementmentioning
confidence: 99%
“…With respect to the five challenges reported by the authors, GSS proved to be an important tool for knowledge acquisition. Similarly, a study by Oliveira et al (2019) reported the use of computer-interpretable guidelines (CIGs) for knowledge acquisition. According to the authors, CIGs have the ability to facilitate knowledge acquisition through visualization and organization, simplicity and automation, manipulation of knowledge elements and storage and dissemination.…”
Section: Using Knowledge Acquisition Toolsmentioning
confidence: 99%
“…It can also reason about new or hidden knowledge based on known factual knowledge. Ontologies are widely used in many domains, such as information science [30,31], medical science [32,33], and education [34,8].…”
Section: The Ontology In Sarmentioning
confidence: 99%
“…Tiago Oliveira, Gonçalves, Novais, Satoh, and Neves () OWL‐based acquisition and editing of computer‐interpretable guidelines [CIG] with the CompGuide editor, present the characterization of the current landscape of CIG as medium for the delivery of clinical decision support acquisition tools based on the properties of guideline visualization, organization, simplicity, automation, manipulation of knowledge elements, and guideline storage and dissemination. Additionally, they described the CompGuide Editor, a tool for the acquisition of CIGs in their CompGuide model for Clinical Practice Guidelines that also allows the editing of previously encoded guidelines.…”
Section: Guest Editorialmentioning
confidence: 99%